2014
DOI: 10.1093/schbul/sbu029
|View full text |Cite
|
Sign up to set email alerts
|

From Phenomenology to Neurophysiological Understanding of Hallucinations in Children and Adolescents

Abstract: Typically reported as vivid, multisensory experiences which may spontaneously resolve, hallucinations are present at high rates during childhood. The risk of associated psychopathology is a major cause of concern. On the one hand, the risk of developing further delusional ideation has been shown to be reduced by better theory of mind skills. On the other hand, ideas of reference, passivity phenomena, and misidentification syndrome have been shown to increase the risk of self-injury or heteroaggressive behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 102 publications
(111 reference statements)
5
76
0
1
Order By: Relevance
“…Hugdahl suggested hallucinations to be partly caused by reduced inhibitory top-down control in the auditory domain, and proposed that for adequate perception of auditory information, interaction of bottom-up and top-down processes was important (Hugdahl, 2009;Jardri et al, 2014). The findings of this study support the idea of affective ToM impairments as a trait marker of schizophrenia (Bora et al, 2009).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Hugdahl suggested hallucinations to be partly caused by reduced inhibitory top-down control in the auditory domain, and proposed that for adequate perception of auditory information, interaction of bottom-up and top-down processes was important (Hugdahl, 2009;Jardri et al, 2014). The findings of this study support the idea of affective ToM impairments as a trait marker of schizophrenia (Bora et al, 2009).…”
Section: Discussionsupporting
confidence: 75%
“…It is well established that poor ability to attribute mental states (e.g., beliefs, emotions, intentions) to oneself and to others (theory of mind, ToM; Frith, 1992) causes unsuccessful social interactions and social functioning (Brüne, 2005), and impaired ToM was frequently shown in schizophrenia (Hirao et al, 2008;Irani et al, 2006;Kelemen et al, 2005;Kington et al, 2000;Lam et al, 2014;Russell, 2000;Scherzer et al, 2012; for meta-analyses see Bora et al, 2009;Chung et al, 2014;Sprong et al, 2007). Several studies showed that impaired ToM skills were associated with the severity of psychotic symptoms (Bora et al, 2009;Guastella et al, 2013; but see Abdel-Hamid et al, 2009;Urbach et al, 2013), especially with delusions and hallucinations (Corcoran et al, 1995;Frith, 1992;Harrington et al, 2005a;Jardri et al, 2014; for a critical review see Harrington et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…As noted in a review (Waters et al, 2014) the nature of the relationship between hallucinations of different sensory modalities has hardly been examined. Although this situation is not unique for schizophrenia spectrum disorders (Waters et al, 2014), some studies indicate that the prevalence of multimodal hallucinations may be severely underestimated in this group (Goodwin et al, 1971) while others indicate that the presence of MMHs may be indicative of an underlying organic etiology (Roberts, 1984;Albert, 1987), or, in children and adolescents, of a more severe expression of schizophrenia (David et al, 2011;Jardri et al, 2014;Cachia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is stated in many sources that these hallucinations might inhibit, excite or converse stimulants (Ozakkaş, 1985;Jardri, 2014;Kaya et. al., 2015).…”
Section: Introductionmentioning
confidence: 99%